Perbandingan Kurikulum Pendidikan Agama Islam di Indonesia dan Negara Muslim Lainnya - Kota Raja (Jurnal Pendidikan Islam Indonesia, 2025)
This study discusses the comparison of Islamic Religious Education (PAI) curricula in Indonesia and several other Muslim countries. The main focus of the study is on the structure, content, teaching methods, and educational objectives implemented in each country. In Indonesia, the PAI curriculum emphasizes a moderate approach that accommodates diversity and national values, with a focus on character building and moral development. Meanwhile, in other Muslim countries such as Saudi Arabia, Egypt, and Turkey, the PAI curriculum tends to differ in terms of teaching methods, content focus, and religious ideological orientation, which influence the educational patterns. The results show that these curriculum variations are influenced by the unique cultural, political, and social factors in each country. This study is expected to provide a comprehensive overview of the dynamics of Islamic religious education in the Muslim world and serve as a reflection for the development of the PAI curriculum in Indonesia.